IMPLEMENTATION OF ACADEMIC SUPERVISION MANAGEMENT IN PRIMARY SCHOOL TO FACE THE DISRUPTION ERA - Ratnasari, Desi; Roemintoyo, Roemintoyo; Winarno, Winarno (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Supervision is part of school-based management. The implementation of supervision, especially in the field of academics is very important to see the shortcomings of the implementation of learning, in order to always try to improve the quality of education.The purpose of this study to explain the implementation of supervision in primary schools.This study uses descriptive-qualitative research methods. Principals conduct academic supervision of teachers every month. Principals always give feedback to teachers after seeing the implementation of learning to always improve the quality of education. Academic supervision on the performance of teachers in the learning process is very important for teachers to always innovate in the implementation of learning to improve the quality of education in the face of disruption era.